The Classic in Clarice Lispector: the myth as a structuring component in the novel ‘Uma Aprendizagem ou o livro dos prazeres’ - Albertim, Alcione Lucena (Romanitas - Revista de Estudos Grecolatinos, 2021)
The present article aims to analyse the presence of narratives which belong to greek-latin mythic tradition in the romance Uma aprendizagem ou o livro dos prazeres, de Clarice Lispector, identifying it as component of the plot, of narrative construction, structural element inside the story. In this sense, a search for the existent myths in the fiction was fulfilled, making use of classical works such as Metamorphoses, by Ovid, Iliad and Odyssey, by Homer, and Theogony, by Hesiod, in order to verify the correspondence of the myths with the narrative and to analyse its implication in the story’s weaving.
Keywords: Myths; Literature; Poiesis; Narrative